2022
DOI: 10.1177/14680874221117686
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of ammonia-hydrogen peroxide blends in HCCI engine mode

Abstract: The potential use of hydrogen peroxide as an ignition promoter to enable the use of ammonia in compression ignition engines is explored in the current study. A simplified numerical HCCI engine model within the Chemkin Pro suite is employed. The numerical investigation reveals that the proposed use of hydrogen peroxide is significantly more advantageous against the more conventional method of preheating the intake charge to achieve ignition, whilst using a glow plug. In particular, the IMEP, power and torque ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The water present in the aqueous ammonia obviously compounded the problem of cooling the ignition zone with water, making ignition even more difficult than for anhydrous ammonia. 13 In the case of aqueous ammonia with NH 4 NO 2 , the temperature within the ignition Zone 1 dropped initially, but then increased once ignition began. The heat release and expansion of gases in Zone 1 also resulted in an increased of the temperature of the bulk gases in Zone 2, by compression and by heat transfer.…”
Section: Ammonium Nitritementioning
confidence: 99%
See 1 more Smart Citation
“…The water present in the aqueous ammonia obviously compounded the problem of cooling the ignition zone with water, making ignition even more difficult than for anhydrous ammonia. 13 In the case of aqueous ammonia with NH 4 NO 2 , the temperature within the ignition Zone 1 dropped initially, but then increased once ignition began. The heat release and expansion of gases in Zone 1 also resulted in an increased of the temperature of the bulk gases in Zone 2, by compression and by heat transfer.…”
Section: Ammonium Nitritementioning
confidence: 99%
“…Shafiq and Efstathios-Al 13 investigated the possibility of reducing ignition delays in a high-speed Homogeneous Charge Compression Ignition (HCCI) engine using hydrogen peroxide (H 2 O 2 ). They found that H 2 O 2 was very effective in increasing engine load and decreasing NOx emissions, when compared with intake air preheating.…”
Section: Introductionmentioning
confidence: 99%
“…In order to take advantage of decarbonized combustion with ammonia, other research has tried to find solutions to improve ammonia combustion. Shafiq and Omar [24] employed hydrogen peroxide as an ignition promoter to facilitate the utilization of ammonia. The results showed a significant increase in indicated engine power and torque, as well as a dramatic reduction in NO x emissions.…”
Section: Introductionmentioning
confidence: 99%